Evaluasi Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) pada Rumah Sakit Bhayangkara Yogyakarta - Kristiawati, Chindy; Syaodih, Erliany; Mulyani, Kahar (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Hospital Management Information System is an integrated information system that plays an important role in supporting hospital operations through the use of information technology. Bhayangkara Yogyakarta Hospital has implemented SIMRS since 2016 but until now there has never been an evaluation related to the implementation of the role of SIMRS. The purpose of this study was to determine whether SIMRS at Bhayangkara Hospital can improve service efficiency, act as operational control, management control and strategy planning. This type of research is descriptive qualitative with interview method. Informants in this study are the Head of Management, Head of Finance, Head of SIMRS, admissions staff, medical records staff, outpatient staff, pharmacy staff and cashier staff. Data analysis used in this study with the method of analyzing and evaluating information systems. The results showed that the application of hospital management information systems in Bhayangkara Hospital is in accordance with its role in improving service efficiency, as operational control, management control and strategy planning. From the results of the study it can be concluded that SIMRS facilitates and improves employee performance so as to improve service efficiency. SIMRS improves hospital operational control with more effective and efficient information in terms of service processes to operational costs. With SIMRS, the continuity of Bhayangkara Hospital management system is easier and controlled with an automated system. SIMRS provides accurate data that facilitates decision making in developing strategies and policies.